A large-scale brain network of species-specific dynamic human body perception. (February 2023) - Li, Baichen; Solanas, Marta Poyo; Marrazzo, Giuseppe; Raman, Rajani; Taubert, Nick; Giese, Martin; Vogels, Rufin; de Gelder, Beatrice
Abstract: This ultrahigh field 7 T fMRI study addressed the question of whether there exists a core network of brain areas at the service of different aspects of body perception. Participants viewed naturalistic videos of monkey and human faces, bodies, and objects along with mosaic-scrambled videos for control of low-level features. Independent component analysis (ICA) based network analysis was conducted to find body and species modulations at both the voxel and the network levels. Among the body areas, the highest species selectivity was found in the middle frontal gyrus and amygdala. Two large-scale networks were highly selective to bodies, dominated by the lateral occipital cortex and right superior temporal sulcus (STS) respectively. The right STS network showed high species selectivity, and its significant human body-induced node connectivity was focused around the extrastriate body area (EBA), STS, temporoparietal junction (TPJ), premotor cortex, and inferior frontal gyrus (IFG). The human body-specific network discovered here may serve as a brain-wide internal model of the human body serving as an entry point for a variety of processes relying on body descriptions as part of their more specific categorization, action, or expression recognition functions. Highlights: Weith ultra-high-field fMRI, multispecies videos, and data-driven methods. Contrasting human and monkey videos reveals human body specificity of selective nodes of the network. We propose a novel role for this network in anchoring various more specific aspects of social perception.